An Interactive Design Framework to Explore Fault-Tolerant and Low-Energy Reconfigurable Architectures - Simpson, Zachary; Nguyen, Linh; Drewfs, Natalie; Mehta, Gayatri (European Journal of Applied Sciences, 2021)
Domain-specific customized reconfigurable architectures show great promise for low energy applications as they can be tailored according to the suite of applications. In order to design new optimized architectures, we need to be able to consider and evaluate tradeoffs, and explore design choices efficiently. In this paper, we present an interactive design framework to explore low energy and fault-tolerant reconfigurable architectures. This allows users to experiment their ideas, try out-of-the-box strategies, and analyze their results visually. This can help designers and researchers understand the bottlenecks and constraints of different approaches in a better way. This can also help students learn digital design and reconfigurable computing concepts in a fun and interactive way. The framework has two gameplay modes – single player and community play. In single player version, users can work on their individual levels where as community play allows users to build upon other users’ solutions. The game offers in-depth tutorials over the variety of gameplay elements as well as give users insight on how the game elements relate to the critical design concerns of reconfigurable architectures, such as, power, performance, area, and fault tolerance.